SUSTAINABLE STRATEGIES, DIGITAL CIRCULAR ECONOMY, AND BRAND PURPOSE RECONFIGURATION IN RETAIL - Silva, Maria de Lurdes Correia da; Vargas-Sánchez, Alfonso (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
The transition to a digital circular economy poses a paradox for established (legacy) brands: how can they reconfigure their purpose to thrive in the recommerce sector, abandoning their linear logic? Existing literature addresses brand purpose and recommerce separately, undertheorizing how purpose can function as a strategic mechanism to mitigate consumer distrust, a central barrier in the digital secondhand market. This article fills this gap by proposing a conceptual model that explains how an authentic purpose, focused on circularity, shapes consumer behavior. Through an inductive case study of IKEA, we verify how a genuine purpose transcends ethical value, acting as a catalyst that amplifies the dimensions of hedonic, social, and functional value. Fundamentally, it operates as a risk mitigator, reinforcing trust and perceived functional value. We conclude that brand purpose, when authentically operationalized, becomes the central strategic asset for creating multidimensional value and success in circular retail, offering a roadmap for leadership in the sustainable digital economy.